BLOCKCHAIN DAN SMART CONTRACT: IMPLEMENTASI SUKUK DIGITAL DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITS DI ERA GREEN FINANCE - Fadillah, Nur; Mustofa (ITB AAS Indonesia Surakarta, 2025)
Sukuk have emerged as a key instrument in supporting sustainable financing, particularly in Indonesia, which pioneered its publication in 2018. However, transparency in fund use, reporting accountability, and adherence to international Environmental, Social, and Governance (ESG) standards remain key challenges. This study aims to analyze the role of smart contracts in strengthening the transparency and accountability of green finance-based digital sukuk, emphasizing their relevance to the maqasid al-shariah (Islamic principles). The research method employed a descriptive qualitative approach with a literature review. Secondary data were sourced from academic literature, official regulatory reports, and relevant industry practice documents. The results of the study indicate that the integration of blockchain-based smart contracts in green sukuk can improve issuance efficiency, reduce operational costs by reducing the role of intermediaries, and ensure transparency through permanent recording. In terms of accountability, smart contracts are able to automatically execute yield payments and principal repayments according to the contract, while simultaneously ensuring that funds are truly allocated to green projects. These findings also confirm the alignment of smart contracts with the maqasid al-shariah, particularly in the aspects of property protection (hifz al-mal), justice (al-adl), and environmental protection (hifz al-bi’ah). This study differs from previous studies that only analyzed regulatory and market aspects, this study offers a framework for integrating smart contracts based on maqasid al-shariah in green sukuk.